2017
DOI: 10.1299/jamdsm.2017jamdsm0058
|View full text |Cite
|
Sign up to set email alerts
|

Improving the energy efficiency of bipedal robots with bi-articular actuation

Abstract: The goal of this study is to investigate the effect of actuator position on the theoretical energy consumption of an electrically powered bipedal robot. Specifically, the study focuses on the legs of the afore-mentioned robot because their function is limited, as they are primarily used for either locomotion or standing, and thus, this is suitable for optimization. Furthermore, the hip and knee joints constitute the most powerful joints, and thus, these are studied first. A mathematical formulation is adopted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…10,11 BA offers the possibility to transfer mechanical power between joints, 12 in particular from proximal toward distal joints, 13 leading to an improvement in energy efficiency. 14 For example, Oh et al 15 have shown that having biarticular muscles helps to increase the energy efficiency for human and animal motion.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 BA offers the possibility to transfer mechanical power between joints, 12 in particular from proximal toward distal joints, 13 leading to an improvement in energy efficiency. 14 For example, Oh et al 15 have shown that having biarticular muscles helps to increase the energy efficiency for human and animal motion.…”
Section: Introductionmentioning
confidence: 99%
“…Eight different actuation setups were also investigated based on three linear mono-articular and bi-articular actuators to select the preferable actuation configuration [9]. An investigation on the impact of the position and orientation of the biarticular actuator on the energy usage of an electrically driven bipedal robot was conducted [10]. A number of various actuation configurations were evaluated using the Genetic Algorithm (GA) to find the configuration that results in the least amount of energy during standing and stepping phases.…”
Section: Introductionmentioning
confidence: 99%
“…As its name suggests, BA means simultaneous actuation of two joints of the robot by only one actuator [11] or a passive component like a spring [12]. BA offers the possibility to transfer mechanical power between joints [13], in particular from proximal towards distal joints [14], leading to an improvement in energy efficiency [15]. Such actuation also produces a maximum end-effector force in a more homogeneously distributed way [16], eases the control [17], and simplifies the dynamic equations [18].…”
Section: Introductionmentioning
confidence: 99%